High resolution computed tomography pattern of usual interstitial pneumonia in rheumatoid arthritis-associated interstitial lung disease: Relationship to survival - Yunt, Zulma X.; Chung, Jonathan H.; Hobbs, Stephen; Fernandez-Perez, Evans R.; Olson, Amy L.; Huie, Tristan J.; Keith, Rebecca C.; Janssen, William J.; Goldstein, Barbara L.; Lynch, David A.; Brown, Kevin K.; Swigris, Jeffrey J.; et al. (Respiratory medicine, 2017)
Interstitial lung disease is a common extra-articular manifestation of rheumatoid arthritis (RA-ILD) and is associated with significant morbidity and mortality. However, limited data exist regarding predictors of mortality. We sought to examine the prognostic value of the high-resolution computed tomography (HRCT) patterns in patients with RA-ILD. RA-ILD patients with HRCT patterns of usual interstitial pneumonia (UIP) or nonspecific interstitial pneumonia (NSIP) were identified among a longitudinal cohort of individuals evaluated at National Jewish Health. A total of 158 subjects were included in the study. For each subject, the earliest available HRCT was reviewed independently by two expert thoracic radiologists blinded to clinical data. HRCT patterns were classified as demonstrating definite UIP, possible UIP, or NSIP. Kaplan-Meier curves were generated and survival was compared among the three patterns using a log rank test for trend. One hundred subjects (63%) had HRCT findings classified as definite UIP, 23 (15%) as possible UIP and 35 (22%) as NSIP. No difference in survival was seen between subjects with definite UIP versus those with possible UIP. The combined group of subjects with either definite- or possible UIP had significantly worse survival than those with NSIP (log-rank p = 0.03). In patients with RA-ILD, patients with either definite UIP or possible UIP have equally poor survival when compared to those with an NSIP pattern. •This study is the first to evaluate the prognostic utility of radiologic UIP classification in RA-ILD.•There is survival difference among RA-ILD patients with definite UIP versus possible UIP.•Patients with RA-ILD and definite or possible UIP on HRCT have worse outcome relative to those with NSIP.